Studies on Sacred Groves and Sacred Trees along the Eastern Bank of River Hoogly of North 24 Parganas, West Bengal - Chakraborti, Udipta; Biswas, Olive; Das, Aditya Kumar; Roy, Sankarsan; Das, Priyanka; Mitra, B. (Indian Forester, 2016)
The aim of the study is to inventorise and portray the present status of sacred groves and sacred trees (SGs&STs) spreaded over the eastern bank of the river Hoogly of North 24 Parganas, West Bengal. Among 129 SGs and STs reported here, 84 SGs and STs are found as well maintained (65.1%) and followed by 29 irregularly maintained (24%) 15 deserted (11.6 %) and the rest one of occasional use. Among the eight municipalities, Naihati Municipality is carrying the maximum number of well maintained SGs and STs and Titagarh Municipality is accompanied with the highest number of deserted SGs and STs. All these sacred areas are under threat due to urbanization. Replacement with idols and concrete structures may lead to Traditional Conservation.